2004
DOI: 10.1111/j.0962-1075.2004.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a gut‐specific cathepsin L from the aphid Aphis gossypii

Abstract: We have characterized proteinase activities in gut extracts from the cotton-melon aphid (Aphis gossypii Glover), an insect feeding strictly on protein-poor phloem. The major, if not exclusive, intestinal proteinases of this aphid are of the cysteine type. A cDNA has been cloned from a gut library and codes for the cysteine proteinase AgCatL, a cathepsin L-like cysteine proteinase. The AgCatL protein shows high sequence similarity with mammalian and some arthropod cathepsin L-like proteinases, but can be reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 53 publications
2
43
0
1
Order By: Relevance
“…Other contigs with putative functional importance for aphid host-plant interaction, including chemosensory proteins (Table 1), are related to sensing and tasting of plant compounds (Wanner et al, 2005), which have been (Cristofoletti et al, 2003;Rahbé et al, 2003;Deraison et al, 2004).…”
Section: Xenobiotic Detoxificationmentioning
confidence: 99%
“…Other contigs with putative functional importance for aphid host-plant interaction, including chemosensory proteins (Table 1), are related to sensing and tasting of plant compounds (Wanner et al, 2005), which have been (Cristofoletti et al, 2003;Rahbé et al, 2003;Deraison et al, 2004).…”
Section: Xenobiotic Detoxificationmentioning
confidence: 99%
“…Essential amino acids are also supplied by the presence of symbionts (Douglas, 1998). However, studies have now demonstrated the presence of proteases within the gut of aphids (Cristofoletti et al, 2003(Cristofoletti et al, , 2006Deraison et al, 2004), suggesting that they are capable of digestive proteolysis. The aphid A. pisum has a midgut aminopeptidase (Rahbé et al, 1995) and a cathepsin-L-like cysteine proteinase (Cristofoletti et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The aphid A. pisum has a midgut aminopeptidase (Rahbé et al, 1995) and a cathepsin-L-like cysteine proteinase (Cristofoletti et al, 2003). The occurrence of a cysteine proteinase may be general among aphids since a similar enzyme was found in Brevicoryne brassicae (L.) (Silva et al, 2010) and a candidate cathepsin-L was cloned from Aphis gossypii (Glover) (Deraison et al, 2004). A cysteine proteinase inhibitor, oryzacystatin I (OC-I), has been shown to be active in M. persicae, successfully decreasing endogenous protease activity .…”
Section: Discussionmentioning
confidence: 99%
“…There are also considerable variations in stomach pH. Altohugh the pH in the stomach of aphids was estimated to be approximately 5.0-6.0 (Deraison et al, 2004), the pH in the midgut of S. exigua is much more alkaline with values ranging from 8 to 11 (own unpublished results). In addition, a potential reason for the different toxicity can also be the binding of the lectin to cells, its entry into the cells, intracellular routing, and degradation of the protein.…”
Section: Toxicity Of Elderberry Rip Lectin In Insectsmentioning
confidence: 98%